Why apparel companies go green?. (15th September 2021) - Dixit, Jasmine S.; Alavi, Shirin; Ahuja, Vandana
The environmental pollution has compelled apparel brands in India as well as international markets to adopt green based strategies. Such strategies help organisations build a loyal consumer base. It is imperative to explore the motivations and challenges faced by firms producing green apparel, more so given the limited research available on this topic in the academic literature. This qualitative research study aims to explore not only the motivations and challenges faced by these firms to make green offerings but also the perceived effectiveness of the green brands produced by apparel companies. For this purpose, semi-structured interviews were conducted with the managers of firms producing green apparels. The findings indicate that consumer awareness and brand aspirations are the main motivators for firms to go green. The effectiveness of going green for brands can be summarised under the heads of brand image enhancement, competitive advantage, cluster creations and rural support.